2016
DOI: 10.1002/2016gl071306
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical imaging of shallow degassing in a Yellowstone hydrothermal system

Abstract: The Yellowstone Plateau Volcanic Field, which hosts over 10,000 thermal features, is the world's largest active continental hydrothermal system, yet very little is known about the shallow “plumbing” system connecting hydrothermal reservoirs to surface features. Here we present the results of geophysical investigations of shallow hydrothermal degassing in Yellowstone. We measured electrical resistivity, compressional‐wave velocity from refraction data, and shear wave velocity from surface‐wave analysis to image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 66 publications
(71 reference statements)
0
40
0
Order By: Relevance
“…Our study builds upon previous geophysical studies that imaged subsurface structures, fluid flow pathways, and hydrothermal alteration in volcano‐hydrothermal systems (e.g., Aizawa et al, ; Bouligand et al, ; Byrdina et al, ; Finn et al, ; Finn & Morgan, ; Gresse et al, , ; Hase et al, ; Pasquet et al, ; Revil et al, ; Rosas‐Carbajal et al, ; Soengkono, ). In contrast to many of these studies that used a single geophysical method and often resulted in a nonunique interpretation, we combine several different geophysical methods and quantify the spatial relationships among the diverse data sets.…”
Section: Introductionmentioning
confidence: 65%
“…Our study builds upon previous geophysical studies that imaged subsurface structures, fluid flow pathways, and hydrothermal alteration in volcano‐hydrothermal systems (e.g., Aizawa et al, ; Bouligand et al, ; Byrdina et al, ; Finn et al, ; Finn & Morgan, ; Gresse et al, , ; Hase et al, ; Pasquet et al, ; Revil et al, ; Rosas‐Carbajal et al, ; Soengkono, ). In contrast to many of these studies that used a single geophysical method and often resulted in a nonunique interpretation, we combine several different geophysical methods and quantify the spatial relationships among the diverse data sets.…”
Section: Introductionmentioning
confidence: 65%
“…Poisson's ratio increases as fluid saturation increases (Bachrach et al, 2000;Dvorkin and Nur, 1996;Nur and Simmons, 1969;Salem, 2000). Furthermore, Poisson's ratio is an indicator for determining the difference between gas and fluid saturated materials (Gregory, 1976;Pasquet et al, 2016) and has been shown to be useful to track pressure changes (Prasad, 2002), map the water table depth (Bachrach et al, 2000;Pasquet et al, 2015b;Salem, 2000;Uyanık, 2011), and differentiate gas and fluid in hydrothermal systems (Pasquet et al, 2016). To image the water table with Poisson's ratio, the conceptual model of the geology must be simplified (i.e.…”
Section: Poisson's Ratiomentioning
confidence: 99%
“…For applications to characterize the critical zone, it is possible to combine Pand S-wave refraction tomography [18,19] or to use surface-wave profiling methods [20,21]. These approaches have been tested in further studies [22,23] and applied for quantitative estimations of hydrological parameters in hydrothermal contexts [24]. Nevertheless, there are inherent incompatibilities between P-wave tomography and surface-wave analysis as they involve distinct wavefield examinations and different assumptions about the medium and, as a result, V P and V S models have contrasting resolutions, investigation depths, and posterior uncertainties.…”
Section: Introductionmentioning
confidence: 99%